(untitled) (Eurasian Medical Research Periodical, 2022)
Recent studies indicate an increasing role in the development of bronchopulmonary diseases in children of atypical pneumotropic pathogens such as Mycoplasma pneumoniae, Chlamydop hilapneumoniae, respiratory viruses, etc. The term "atypical pneumonia" (caused by these pathogens) was introduced 20-30 years ago due to their different from typical pneumonia caused by extracellular agents - streptococci, staphylococci, etc., course, as well as difficulty and the rarity of their detection in past years. Today the situation has changed. The technical and methodological possibilities of diagnosing these infections have appeared and approaches to the etiotropic treatment of diseases caused by them have been determined